School Psychology Unified Antiracism Statement and Call to Action. Issue 3 (14th September 2020) - García-Vázquez, Enedina; Reddy, Linda; Arora, Prerna; Crepeau-Hobson, Franci; Fenning, Pamela; Hatt, Clifford; Hughes, Tammy; Jimerson, Shane; Malone, Celeste; Minke, Kathleen; Radliff, Kisha; Raines, Tara; et al.
Abstract: As school psychologists, we have an ethical responsibility to engage in social justice and antiracist action. School psychology organizations and graduate education programs play an important role in shaping future generations of school psychologists to lead the mental health, educational and research, and advocacy initiatives that promote equity for school personnel, students, families and communities they serve. This is only possible if our field acknowledges, evaluates, and works to reconstruct existing systems, structures, and policies that lead to inequitable outcomes for some groups and not others. "How can the school psychology community serve the diverse society in which we live without explicit and intentional education and growth in this area?" To help answer this question, APA Division 16, Trainers of School Psychologists, Council of Directors of School Psychology Programs, Society for the Study of School Psychology, the American Board of School Psychology, and the National Association of School Psychologists have come together to reaffirm our commitment to ensure current and future school psychologists are empowered to be antiracist agents of change. Impact Statement School Psychology's commitment and mission to advance research, practice, policy and advocacy for education continues. In light of this tragedy, we have a sharpened focus to reduce systemic racism and inequities in schools and communities across our nation. We must take affirmative action through active antiracist work.